A Novel MTTK Gene Variant m.8315A>C as a Cause of MERRF Syndrome - Štufková, Hana; Kolářová, Hana; Lokvencová, Kateřina; Honzík, Tomáš; Zeman, Jiří; Hansíková, Hana; Tesařová, Markéta (Genes, 2022)
In this study, we report on a novel heteroplasmic pathogenic variant in mitochondrial DNA (mtDNA). The studied patient had myoclonus, epilepsy, muscle weakness, and hearing impairment and harbored a heteroplasmic m.8315A>C variant in the MTTK gene with a mutation load ranging from 71% to >96% in tested tissues. In muscle mitochondria, markedly decreased activities of respiratory chain complex I + III and complex IV were observed together with mildly reduced amounts of complex I and complex V (with the detection of V*- and free F1-subcomplexes) and a diminished level of complex IV holoenzyme. This pattern was previously seen in other MTTK pathogenic variants. The novel variant was not present in internal and publicly available control databases. Our report further expands the spectrum of MTTK variants associated with mitochondrial encephalopathies in adults.
Keywords: MTTK gene; m.8315A> C; mitochondriální DNA; Humans; respirační komplex IV; dospělí; mitochondriální encefalomyopatie; svalové mitochondrie; MERRF Syndrome; mtDNA; Mitochondria, Muscle; DNA, Mitochondrial; syndrom MERRF; lidé; Electron Transport Complex IV; Mitochondrial Encephalomyopathies; heteroplasmy; Adult; OXPHOS